2019
DOI: 10.1029/2018jd029852
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Surface Signal of Interannual Variability of Boreal Stratospheric Final Warmings

Abstract: Springtime stratospheric final warming (SFW) variability has been suggested to be linked to the tropospheric circulation, particularly over the North Atlantic sector. These findings, however, are based on reanalysis data that cover a rather short period of time (1979 to present). The present work aims to improve the understanding of drivers, trends and surface impact of dynamical variability of boreal SFWs using chemistry‐climate models. We use multidecadal integrations of the fully coupled chemistry‐climate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 58 publications
5
37
0
Order By: Relevance
“…Provided that the average length of an SSW event is limited and there will be repetition of zonal wind reversal between westerlies and easterlies, no new SSW events will be defined again within 20 consecutive days after a former SSW event is identified already [8,9]. In addition, stratospheric final warming is excluded as the zonal mean zonal winds change from westerlies to easterlies and stay unchanged in the direction since it marks the annual cycle of the stratospheric circulation from wintertime to summertime [54].…”
Section: Methodsmentioning
confidence: 99%
“…Provided that the average length of an SSW event is limited and there will be repetition of zonal wind reversal between westerlies and easterlies, no new SSW events will be defined again within 20 consecutive days after a former SSW event is identified already [8,9]. In addition, stratospheric final warming is excluded as the zonal mean zonal winds change from westerlies to easterlies and stay unchanged in the direction since it marks the annual cycle of the stratospheric circulation from wintertime to summertime [54].…”
Section: Methodsmentioning
confidence: 99%
“…Once a major SSW is defined, there will not be any new SSW events defined repeatedly within 20 consecutive days afterward [4,33,43]. Furthermore, stratospheric final warming is excluded as the zonal mean zonal wind reversal from westerlies to easterlies marks the annual cycle of the stratospheric circulation from wintertime to summertime [46].…”
Section: Methodsmentioning
confidence: 99%
“…thus decrease the zonal wind below, while for 1 hPa-first events the PWs break around 1 hPa (Hardiman et al, 2011;Thiélemont et al, 2019).…”
Section: 1029/2020jd034353mentioning
confidence: 96%
“…However, they also found that winters without a SSW are followed by 1 hPa-first SFW which we cannot confirm with our analysis. One possible explanation for this discrepancy may be that Thiélemont et al (2019) used model data (CESM/WACCM) that include significantly less 10 hPa-first SFW events compared to ERA-Interim. However, we also note, that for single cases the 10 hPa-first and 1 hPa-first classification might be different especially for the no negative NAM spring transition where the average onset days at 10 and 0.7 hPa are close together.…”
Section: Tablementioning
confidence: 99%